Over the wall - Fabry, Chris, 1961- (Carol Stream, Ill. : Tyndale House, 2007)
Jamie's parents try to get her to trust God to help to decide what to do after she is accepted at an elite NASCAR training school sponsored by a competing racing team.
6.4
5-8
Keywords: NASCAR (Association) -- Juvenile fiction; NASCAR (Association) -- Fiction; NASCAR (Association) -- Fiction; Automobile racing -- Juvenile fiction; Christian life -- Juvenile fiction; Families -- Juvenile fiction; Foster home care -- Juvenile fiction; Automobile racing -- Fiction; Christian life -- Fiction; Family life -- Fiction; Foster home care -- Fiction; Automobile racing -- Fiction; Christian life -- Fiction; Family life -- Fiction; Foster home care -- Fiction; North Carolina -- Juvenile fiction; North Carolina -- Fiction; North Carolina -- Fiction